2009
DOI: 10.1016/j.neurobiolaging.2007.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Atrophy progression in semantic dementia with asymmetric temporal involvement: A tensor-based morphometry study

Abstract: We performed a longitudinal anatomical study to map the progression of gray matter atrophy in anatomically defined predominantly left (LTLV) and right (RTLV) temporal lobe variants of semantic dementia (SD). T1-weighted MRI scans were obtained at presentation and one-year followup from 13 LTLV, 6 RTLV, and 25 control subjects. Tensor-based morphometry (TBM) in SPM2 was applied to derive a voxel-wise estimation of regional tissue loss over time from the deformation field required to warp the follow-up scan to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
181
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(204 citation statements)
references
References 61 publications
22
181
1
Order By: Relevance
“…17,18 Though the methodology was different, the results from the semantic subtype study, which showed a posterior spread of temporal atrophy and decline in word comprehension, were consistent with our findings. Other studies have examined neuropsychological decline in PPA but have not quantified changes in atrophy.…”
Section: Discussionsupporting
confidence: 87%
“…17,18 Though the methodology was different, the results from the semantic subtype study, which showed a posterior spread of temporal atrophy and decline in word comprehension, were consistent with our findings. Other studies have examined neuropsychological decline in PPA but have not quantified changes in atrophy.…”
Section: Discussionsupporting
confidence: 87%
“…We further investigated the reliability of focal atrophy across individual patients and found that 100% of individuals in both svPPA samples had one of their maximally atrophic points in the same temporopolar region. Beyond the anterior temporal cortex, patients with svPPA exhibit less prominent neurodegeneration in distributed cortical and subcortical regions (Mummery et al, 2000;Rosen et al, 2002;Gorno-Tempini et al, 2004;Brambati et al, 2009;Rohrer et al, 2009). As predicted, the focal atrophy point identified in our cortical thickness analysis was interconnected with a network of brain regions in healthy adults that closely resembled the distributed cortical atrophy pattern of svPPA patients, replicating previous findings .…”
Section: Discussionsupporting
confidence: 88%
“…It is very likely, however, that atrophy in these subjects will eventually spread to involve the right temporal lobe, as has been suggested by a couple of longitudinal studies in semantic dementia. 39,40 An unexpected finding was the fact that the prosopagnosia subjects had a higher female to male ratio than the subjects without prosopagnosia. Given that we have a relatively small sample size this could have occurred by chance.…”
Section: Resultsmentioning
confidence: 99%